From Theory to Practice: What does the Metaphor of Scaffolding Mean to Educators Today? - Verenikina, Irina (Outlines. Critical Practice Studies, 2004)
The current emphasis on rising educational standards in Australian society (eg A Commonwealth Government Quality Teacher Initiative, 2000) has stimulated a growing interest in Vygotsky’s socio-cultural theory widely renowned for its profound understanding of teaching and learning. The metaphor of scaffolding commonly viewed as underpinned by socio-cultural theory and the zone of proximal development in particular, has become increasingly popular among educators in Australia (Hammond, 2002). Teachers find the metaphor appealing as it "offers what is lacking in much literature on education - an effective conceptual metaphor for the quality of teacher intervention in learning" (Hammond, 2002, p.2). However, there is no consensus of opinion among educators on the specific characteristics that constitute successful scaffolding. On the contrary, the current interpretation of scaffolding seems to have been drifting away from the Vygotskian view of teaching and learning and appears to have become an umbrella term for any kind of teacher support (Jacobs, 2001) and therefore, cannot serve the purpose of justifying the quality of teacher intervention. Furthermore, when taken out of its theoretical context, scaffolding tends to be interpreted as a form of direct instruction (Donovan & Smolkin, 2002), which invalidates the Vygotskian idea of teaching as co-construction of knowledge within student-centred activities. Such an interpretation of the metaphor of scaffolding is an unfortunate step back to a traditional, pre-Piagetian way of teaching which is adult-driven in nature and often results in "the imposition of a structure on the student" (Searle, 1984, in Stone, 1998, p. 349). In spite of a number of limitations of the metaphor, that have been discussed by socio-cultural theorists (e. g., Stone, 2001), it remains highly popular among educators. To fulfil teachers’ expectations of scaffolding as being an effective teaching tool, it needs to be understood within the framework of its underlying theory. This project aims to analyse understanding of the concept of scaffolding by educational researchers and practitioners in its connection to the Vygotskian view of the role of instruction in nurturing children as active learners.